Could Uranus and Neptune form by collisions of planetary embryos?. Issue 2 (9th January 2021) - Chau, Alice; Reinhardt, Christian; Izidoro, André; Stadel, Joachim; Helled, Ravit
ABSTRACT: The origin of Uranus and Neptune remains a challenge for planet formation models. A potential explanation is that the planets formed from a population of a few planetary embryos with masses of a few Earth masses which formed beyond Saturn's orbit and migrated inwards. These embryos can collide and merge to form Uranus and Neptune. In this work, we revisit this formation scenario and study the outcomes of such collisions using 3D hydrodynamical simulations. We investigate under what conditions the perfect-merging assumption is appropriate, and infer the planets' final masses, obliquities, and rotation periods, as well as the presence of proto-satellite discs. We find that the total bound mass and obliquities of the planets formed in our simulations generally agree with N -body simulations therefore validating the perfect-merging assumption. The inferred obliquities, however, are typically different from those of Uranus and Neptune, and can be roughly matched only in a few cases. In addition, we find that in most cases, the planets formed in this scenario rotate faster than Uranus and Neptune, close to break-up speed, and have massive discs. We therefore conclude that forming Uranus and Neptune in this scenario is challenging, and further research is required. We suggest that future planet formation models should aim to explain the various physical properties of the planets such as their masses, compositions, obliquities, rotation rates, and satellite systems.